Feminism, Left and Rights in the Age of the Neoliberal Revolution - Caviglia, Alessandro (2018)
This paper addresses the issue of right and left feminism in the context of the neoliberal revolution. To do this, it begins by examining the discussion on whether a right-wing feminism is possible with the aim to frame the discussion in such a manner that allows us to see it in light of the neoliberal era and to bring to the table the distinction between oppression and exploitation. In a second part of the paper, the current debate on feminism and abuse is examined through the debate generated by the Charter of French intellectuals against the #metoo movement, the intervention of Mario Vargas Llosa regarding a supposed feminist inquisition in literature and in art, and the controversial attacks of Camille Paglia against contemporary feminism. The paper ends by articulating both parts and exploring two tensions in the feminist debate.